# Class 11 NCERT Solutions- Chapter 9 Sequences And Series – Exercise 9.3 | Set 2

### Question 17. If the 4^{th}, 10^{th} and 16^{th} terms of a G.P. are x, y, and z, respectively. Prove that x, y, z are in G.P.

**Solution:**

Let the first term of G.P. be a and common ratio be r.

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.According to the question

a

^{4}= ar^{3 }= x ……(1)a

_{10}= ar^{9}= y ……(2)a

_{16}= ar^{15}= z ……(3)Now divide eq(2) by (1), we get

ar

^{9}/ar^{3 }= y /xr

^{6 }= y /xDivide eq(3) by (2), we get

ar

^{15}/ar^{9 }= z/yr

^{6 }= z/yy /x = z/y

^{ }So x, y, z are in G.P.

### Question 18. Find the sum to n terms of the sequence, 8, 88, 888, 8888…

**Solution:**

According to the question

Given Sequence: 8, 88, 888, 8888…

This sequence is neither A.P. nor G.P. but we can change it into G.P.

So, we can write as:

S

_{n }= 8 + 88 + 888 + 8888 + … + n times= 8(1 + 11 + 111 + 1111 + … + n times)

= 8/9(9 + 99 + 999 + 9999 + … + n times)

= 8/9((10 – 1) + (10

^{2 }– 1) + (10^{3 }– 1) + (10^{4 }– 1) + … + n times)= 8/9((10 + 10

^{2 }+ 10^{3 }+ 10^{4 }+ … + n times) – (1 + 1 + 1 + 1 + ….+ n terms))As we know that, the sum of n terms of G.P. with 1

^{st}term a & common ratio r is given by=

=

### Question 19. Find the sum of the products of the corresponding terms of the sequences 2, 4, 8,16, 32 and 128, 32, 8, 2, 1/2.

**Solution:**

According to the question

Sequence 1: 2, 4, 8, 16, 32

Sequence 2: 128, 32, 8, 2, 1/2

Product of corresponding terms are

= 2 x 128, 4 x 32, 8 x 8, 16 x 2, 32 x 1/2

= 256, 128, 64, 32, 16

So, the first term(a) = 256

Common ration = 1/2

S

_{5 }= 256[1 – (1/2)^{5}]/1/2= 496

### Question 20. Show that the products of the corresponding terms of the sequences a, ar, ar^{2 }, …ar^{n – 1 }and A, AR, AR^{2}, … AR^{n – 1 }form a G.P, and find the common ratio.

**Solution:**

According to the question

Sequence 1: a, ar, ar

^{2 }, …ar^{n – 1}Sequence 2: A, AR, AR

^{2}, … AR^{n – 1}Prove: aA, arAR, ar

^{2}AR^{2}, ….^{ }ar^{n – 1}AR^{n – 1}from G.PNow we find the common ration of the G.P

r = arAR. aA = rR

Again,

r = ar

^{2}AR^{2}/arAR = rRHence, the sequence form G.P. and the common ratio is rR

### Question 21. Find four numbers forming a geometric progression in which the third term is greater than the first term by 9, and the second term is greater than the 4th by 18.

**Solution:**

Let us considered a be the first term, r be the common ratio and

four numbers in G.P. are a, ar, ar

^{2},ar^{3}According to the question

So, a

_{3}= a_{1}+ 9ar

^{2}= ar + 9ar

^{2 }– ar = 9 ….(1)a

_{2}= a_{4}+ 18ar = ar

^{3}+ 18ar – ar

^{3}= 18 ….(2)Now divide eq(2) by (1), we get

ar – ar

^{3}/ar^{2 }– ar = 18/9ar (1 – r

^{2})/-a(1 – r^{2}) = 2ar/-a = 2

r = -2

Now put the value of r in eq(1), we get the value of a

a(-2)

^{2 }– a(-2) = 9a = 3

Hence, the four numbers in G.P. are 3, 3(-2), 3(-2)

^{2},3(-2)^{3}= 3, -6, 12, -24.

### Question 22. If the p^{ th}, q^{th},^{ }and r^{th} terms of a G.P. are a, b and c, respectively. Prove that a^{q–r}b^{r–p}c^{p–q }= 1.

**Solution:**

Let us considered the 1st term of a G.P. be k and common ratio x.

According to the question

kx

^{p-1 }= a ….(1)kx

^{q-1 }= b ….(2)kx

^{r-1 }= c ….(3)Prove: a

^{q–r}b^{r–p}c^{p–q }= 1Proof:

Lets take L.H.S

i.e., a

^{q–r}b^{r–p}c^{p–q }Now put the value of a, b, c from the above equations,

a

^{q – r}b^{r – p}c^{p – q }= (kx^{p – 1})^{q – r}(kx^{q – 1})^{r – p}(kx^{r – 1})^{p – q }= k

^{0}x x^{0}= 1

L.H.S = R.H.S

### Question 23. If the first and the nth term of a G.P. are a and b, respectively, and if P is the product of n terms, prove that P^{2} = (ab)^{n}.

**Solution:**

According to the question

The first term of the G.P. is a and the last term is b

Let the G.P. are a, ar, ar

^{2},ar^{3}. Here, r be the common ratio.Then b = ar

^{n-1}Now, Product of n terms(P) = a x ar x ar

^{2 }x … x ar^{n-1}P = a

^{n}r^{{1 + 2 + …n – 1} }P = a

^{n}r^{{(n(n – 1)/2} }So, P

^{2}= a^{2n}r^{(n(n – 1) }= [a

^{2}r^{(n – 1)}]^{n}= [a x ar

^{(n – 1)}]^{n}= [ab]

^{n}Hence Proved.

### Question 24. Show that the ratio of the sum of first n terms of a G.P. to the sum of terms from (n + 1)^{th} to (2n)^{th }term is 1/r^{n}.

**Solution:**

Let the first term of G.P. be a and the common ratio be r.

So, the sum of 1st n terms is

According to the question

Sum of (n+1)

^{th}to (2n)^{th}term isThe required ratio is:

### Question 25. If a, b, c and d are in G.P. show that (a^{2 }+ b^{2 }+ c^{2})(b^{2 }+ c^{2 }+ d^{2}) = (ab + bc + cd)^{2}

**Solution:**

According to the question

a, b, c, d are in G.P., so let the common ratio of G.P.be r.

Then b = ar, c = ar

^{2}, d = ar^{3 }Simplifying LHS by putting value of b, c, d

(a

^{2 }+ b^{2 }+ c^{2})(b^{2 }+ c^{2 }+ d^{2}) = (a^{2 }+ a^{2}r^{2 }+ a^{2}r^{4})(a^{2}r^{2 }+ a^{2}r^{4 }+ a^{2}r^{6})= a

^{4}r^{2}(1 + r^{2 }+ r^{4})^{2}Now, simplifying RHS

(ab + bc + cd)

^{2 }= (a^{2}r + a^{2}r^{3 }+ a^{2}r^{5})^{2 }= a^{4}r^{2}(1 + r^{2 }+ r^{4})^{2}LHS = RHS

### Question 26. Insert two numbers between 3 and 81 so that the resulting sequence is G.P.

**Solution:**

Let us considered x1 and x2 be the two numbers in between 3 and 81. So, the G.P. is 3, x1, x2, 81 and

r be the common ratio. First term of the G.P.(a) = 3

So, a

^{4 }= 81(3)r

^{3}= 81r

^{3}= 27r = 3

So, x1 = ar = 3 x 3 = 9

x2 = ar

^{2}= (3)(3)^{2}= 27Hence, the G.P. is 3, 9, 27, 81

### Question 27. Find the value of n so that may be the geometric mean between a and b.

**Solution:**

G.M. between a and b is √ab

On squaring both side we get

ab(a

^{n}+ b^{n})^{2 }= (a^{n + 1}+ b^{n + 1})^{2}ab(a

^{2n}+ b^{2n}+ 2a^{n}b^{n}) = a^{2n + 2}+ b^{2n + 2}+ 2a^{2n + 2}b^{2n + 2}a

^{2n+1}b + ab^{2n+1}+ 2a^{n+1}b^{n+1}= a^{2n + 2}+ b^{2n + 2}+ 2a^{2n + 2}b^{2n + 2}ba

^{2n+1}+ ab^{2n+1 }= a^{2n + 2}+ b^{2n + 2}ab

^{2n+1 }– b^{2n + 2 }= a^{2n + 2 }– ba^{2n+1}ab

^{2n+1 }– b^{2n + 2 }= a^{2n + 2 }– ba^{2n+1}b

^{2n+1 }(a – b) = a^{2n + 1}(a – b)b

^{2n+1 }= a^{2n + 1}a

^{2n+1 }/ b^{2n + 1 }= 1 = (a/b)^{0}(a/b)

^{2n + 1 }= 1 = (a/b)^{0}2n + 1 = 0

n = -1/2

### Question 28. The sum of two numbers is 6 times their geometric mean, show that numbers are in the ratio

**Solution:**

Let the two numbers be a and b.

And G.M. = √ab

According to the question

a + b = 6√ab …..(1)

Squaring on both side, we get

(a + b)

^{2}= 36(ab)As we know that

(a – b)

^{2}= (a + b)^{2 }– 4(ab)So,

(a – b)

^{2}= 36(ab)^{ }– 4(ab)a – b = 4√2√ab ……(2)

Now we add eq(a) and (2), we get

a + b + a – b = 6√ab + 4√2√ab

2a = √ab(6 + 4√2)

a = √ab(3 + 2√2)

Now put the value of a in eq(1), we get the value of b

√ab(3 + 2√2) + b = 6√ab

b = √ab(3 – 2√2)

Now we find the ratio:

a/b = √ab(3 + 2√2)/√ab(3 – 2√2)

= (3 + 2√2)/(3 – 2√2)

### Question 29. If A and G be A.M. and G.M., respectively between two positive numbers, prove that the numbers are

**Solution:**

Let the two numbers be a & b.

A.M = A= (a + b)/2

G.M = G = 2/√ab

So, a + b = 2A ….(1)

G

^{2}= ab ….(2)As we know that

(a – b)

^{2}= (a + b)^{2 }– 4(ab)So,

(a – b)

^{2}= (2A)^{2 }– 4(G^{2})(a – b)

^{2}= 4(A)^{2 }– 4(G^{2})(a – b)

^{2}= 4[(A)^{2 }– (G^{2})](a – b)

^{2}= 4[(A^{ }– G)(A + G)](a – b) = √4[(A

^{ }– G)(A + G)](a – b) = 2√(A

^{ }– G)(A + G) ……(3)Now add eq(1) and (3), we get

2a = 2A + 2√(A

^{ }– G)(A + G)a = A + √(A

^{ }– G)(A + G)Now put the value of a in eq(1), we get

A + √(A

^{ }– G)(A + G) + b = 2Ab = A – √(A

^{ }– G)(A + G)Hence, the two numbers are A ± √(A

^{ }– G)(A + G)

### Question 30. The number of bacteria in a certain culture doubles every hour. If there were 30 bacteria present in the culture originally, how many bacteria will be present at the end of 2^{nd} hour, 4^{th} hour, and n^{th} hour?

**Solution:**

As the count of bacteria doubles after each hour, so at the end of n hours it becomes 2

^{n}times the original count.So, first term(a) = 30, and common ratio(r) = 2

So, a

_{3}= ar^{2}= (30)(2)^{2}= 120At the end of 2

^{nd}hour there are 120 bacteria.a

_{4}= ar^{4}= (30)(2)^{4}= 480At the end of 4

^{nd}hour there are 480 bacteria.a

_{n+1}= ar^{n}= (30)(2)^{n}At the end of n

^{nd}hour there are (30)(2)^{n}bacteria.

### Question 31. What will Rs. 500 amounts to in 10 years after its deposit in a bank which pays an annual interest rate of 10% compounded annually?

**Solution:**

In the end of 1st year, the amount = 500(1 + 1/10) = 500(1.1)

In the end of 2nd year, the amount = 500(1.1)(1.1)

In the end of 3rd year, the amount = 500(1.1)(1.1)(1.1)

…..So on

At the end of 10 year, the amount = 500(1.1)(1.1)(1.1)…….10 times

= 500(1.1)

^{10}

### Question 32. If A.M. and G.M. of roots of a quadratic equation are 8 and 5, respectively, then obtain the quadratic equation.

**Solution:**

Let the roots of the quadratic equation be a and b.

According to the question

A.M. = (a + b)/2 = 8

a + b = 16

G.M. = √ab = 5

ab = 25

Then the quadratic equation using the roots can be written as

x

^{2 }– (a + b)x + ab = 0Now put all these values in the quadratic equation, we get

x

^{2 }– 16x + 25 = 0